Prevalence of surcharge and obesity in children from the public and private education - Carmo, Alcino Manuel do (2012)
The present study has the objective of knowing the predominance of surcharge and obesity in children that study in two schools a private one in Aracaju city and other in Salvador city. A cross section study has been realized with 331 registered students in two schools; one of them is a particular one in Aracaju city and other public one in Salvador. To surcharge definition, the percentage between 85 and 97 was considered; to obesity diagnosis, the percentage of 97 or more. It wasn’t identified significant difference according to the surcharge in children of both sexs in the two mentioned schools. It was noticed a significant difference related to obesity. In boys, predominance in students of particular schools was 13.58% and in students of public schools was 5.37%. In girls, it was 10.93% in students of particular schools and 4.3% in students of public schools. The relavant increase in surcharge and obesity predominance in children which is between 4 and 12 years old emphasizes the importance of preventable interventions in this age group, because the earlier we begin these interventions, the better can be the results.